(untitled) (International Journal of Engineering and Computer Science, 2015)
Transmission of data through internet has become very common now a days so, it is important to have secure communication over internet. Cryptography and Steganography are two important methods for providing secure communication. Cryptography converts the message into some gibberish form and Steganography hides the message into some other media file that can be text, image, audio, video etc. In this paper we have explained the concept of cryptography and steganography and have compared them .It also focuses on how combination of cryptography and steganography enhances security